Influence of Self-Efficacy, and Perceived Ease Of Use, Perceived Usefulness Behavioral Intention To Purchase Online In Tokopedia With Perceived Risk, As Variable Mediation - Rosa Merry Yusvita; Vera - Pujani (Makro : Jurnal Manajemen Dan Kewirausahaan, 2020)
Abstract:  This study aims to determine the effect of self-efficacy, and Perceived Ease of Use, Perceived Usefulness Against Behavioral Intention in TOKOPEDIA Online Purchase Transactions with Perceived Risk, as a mediating variable (Study in Padang City Communities) ". This research is explanatory with quantitative methods. The sampling technique used in this study was purposive sampling for customers who had shopped at the Tokopedia site, with a sample of 135 respondents. this research uses Partial Least Square with SmartPLS 3.0 program. The Results Showed that Self -efficacy, Perceived Ease of Use, Perceived Usefulness TOKOPEDIA Against Behavioral Intention in Online Purchase Transactions with Perceived Risk, as a mediating variable Self-efficacy Self-efficacy influences behavior towards positivity and significance,then Perceived Ease of Use Perceived Risk, as a mediating variable The implication of this research is to Increase Self-efficacy, Perceived Ease of Use, Perceived Usefulness will Increase Online TOKOPEDIA Behavioral Intention on Purchase Transactions with Perceived Risk, as a mediating variable.